TINGKAT KUALITAS DAN KEAMANAN PRODUK MOLDING MENGGUNAKAN PERSPEKTIF GOOD MANUFACTURING PRACTICES DI BIBIS BAYE KABUPATEN KEDIRI - Lolyka Dewi Indrasari; Ana Komari; Afiff Yudha Tripariyanto; Heribertus Budi Santoso (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
CV. Musta'im produces alphabetical cutting cookies. Alphabetical cutting cookies have alphabetical forms A to Z. Demand for alphabetical cutting cookie products in the last 6 months reaches between 4300 sets to 4500 sets every month. Cookie cutting alphabetical 1 set contains 26 seeds. Pollution occurs is the residue of slab iron that is patchwork. Green manufacturing activities cover production process activities to make it better. The purpose of the activity is to provide socialization in the implementation of good manufacturing practices. Activities with mentoring and reporting to study problems that occur refer to ISO 22000: 2009, ISO 14001: 2015 and HACCP. The implementation of good manufacturing practices has been implemented. SNI ISO 22000: 2009 with a process approach, cv scope. Musta'in, normative reference, food safety management system and management responsibilities have been implemented. ISO 14001:2015 environmental components are not negatively affected, the production stage is waste-friendly, and the recycling process has been carried out. HACCP availability of product information, physical / chemical structure, successive microcidal / static treatment, packaging, storage with cardboard in a non-damp room. Monitoring and evaluation have found problems along with proposed improvements